Wander into Oblivion Peregrinations and the Epiphanio of Justice - A. C. Ljungstrom (Law Text Culture, 2000)
Law is not, it be-comes. Law is not an object but pure be-coming. It is movement. When I act in the world something happens to me. Kairos is Greek for the moment. The true moment. It captures at the same time a centrifugal and centripetal movement. But how does one know in a given moment that it is kairos? Does it only show itself when its all over, when our story is long finished? Is there ever presence in kairos or does every moment point towards an invisible middle, towards a waiting presence, that hides itself? Is kairos about having a feeling for the invisible? Kairos sees law as the infinity of the moment. Within this infinite moment, man is not a master in his own house. Something happens but he doesn't know what it is. He is waiting but he does not know for what. Gorgias makes kairos a central concept in the Rhetoric; it means persuading as an accomplishment of the moment. In his Ethics, Aristotle connects kairos to a poetics of acting – a sense of what comes, what is made possible; and the ethics of the response to the situation. Kairos is everywhere connected with the opposition between contingency and necessity.